Type 2 Diabetes Mellitus and The Risk of Tuberculosis - Sri Rahmayanti Limatahu; Darariani Iskandar; Bulkis Natsir (International Medical Journal Corp. Ltd, 2025)
Type 2 Diabetes Mellitus (T2DM) is a major comorbidity that increases the risk of tuberculosis (TB) through immune system impairment caused by chronic hyperglycemia, including macrophage dysfunction, reduced T-cell activity, oxidative stress, and cytokine imbalance. This literature review aims to analyze the relationship between T2DM and TB from the perspectives of pathophysiology, clinical impact, and healthcare system challenges. The method used is a descriptive narrative based on 10 scientific articles and case reports published between 2020 and 2025, selected through systematic searching. The results show that T2DM contributes to an increased risk of active TB, prolonged treatment duration, lower treatment success rates, and a higher risk of drug resistance. Behavioral factors such as poor glycemic control, smoking habits, and limited access to healthcare further worsen the condition of patients with this comorbidity. On the other hand, bidirectional TB-DM screening efforts in Indonesia have not been optimal due to limitations in training, infrastructure, and inter-program coordination. In conclusion, T2DM increases susceptibility to TB and worsens its progression, highlighting the need for integrated healthcare services, strict blood glucose control, and systemic policy interventions to reduce the morbidity and mortality associated with this comorbidity.